Estimating the impact of household energy savings measures for Ireland using the BER database - Swinand, Gregory P.; O'Mahoney, Amy (Statistical and Social Inquiry Society of Ireland, 2016)
This paper estimates the impacts of various household energy saving measures in Ireland. The analysis develops a matrix of household energy use and types based on the Building Energy Rating (BER) system and the major dwelling and fuel-use types. It explicitly models the difference between using the BER data versus Census data. The analysis uses data from the BER, SEAI, and CSO, and other public sources. Modelling work estimated the distribution of energy ratings for the national sample of households from the BER sample, with the results indicating that the worst energy-rated households were about seven per cent underrepresented in the BER sample. The system, data, and modelled predictions were then used to perform some preliminary cost benefit analysis on energy savings measures versus costs in terms of the overall housing stock in Ireland. The results and model were used by SEAI to inform them of values and options in their energy savings policy work. Indicative results suggest that accounting for underrepresentation of the most inefficient housing units and policies aimed at the lower efficiency units may have the highest ratio of costs over benefits.
read before the Society, 11 February 2016
Keywords: household energy use; Building Energy Rating (BER); Ireland; 314.15